Advances in galvanic corrosion of aluminum alloys. (1st May 2023) - Ruiz-Garcia, A.; Esquivel-Peña, V.; Genesca, J.; Montoya, R.
Abstract: Two lightweight materials were evaluated: a wrought aluminum alloy (AA1) and a cast aluminum alloy (AA2), always coupled to a low-carbon steel (CS). Both the electric potential and pH distributions, of two bare systems (CS-AA1 and CS-AA2) subjected to full immersion conditions in 0.06 M NaCl, are discussed in detail from the experimental and numerical point of views. In conjunction with a miniaturized electrochemical cell and a LAQUAtwin® sensor that allows pH measurements of viscous liquids, solids, and even powder samples, agar hydrogels were used to gather new transient information used to validate a tertiary current distribution model, which was solved by using the finite element method (FEM). The numerical predictions perfectly match with the experimental distributions. The two experimental methodologies exhibit excellent performance for studying galvanic corrosion phenomena, providing reliable and precise results. Graphical abstract: Highlights: Gel technology allowed to validate FEM simulations on the galvanic couple surface. Gel technology allowed to validate FEM simulations of the pH into the electrolyte. Two new experimental methodologies have excellent performance for galvanic couples.